Annual analysis of surface temperature, land cover, and precipitation impacts on durian harvests in Thailand - Lubis, Muhammad Zainuddin; Dwi Wulandari, Pratiwi; Simanjuntak, Andrean V.H.; Batara, B.; Kausarian, Husnul; Anurogo, Wenang; Wedanta Suryadarma, Made; Ansari, Kutubuddin; Jamjareegulgarn, Punyawi (My University, 2026)
This study analyzes the impact of land surface temperature (LST), NDVI, land cover, precipitation, and climatic factors on durian productivity in Thailand (2019–2025). Results show a significant positive correlation between LST and durian yields, particularly in the southern regions, where LST increased by 0.2–0.3 °C. Statistical models indicate that the southern sector will contribute over 50% of the national durian harvest by 2025, with an average yield of 617,990 tons. The precipitation and NDVI trends also correlate with regional variations in yield. The results underscore the complex interactions of temperature, land cover, and precipitation, emphasizing the need for targeted adaptation strategies and integrated planning to sustain agricultural productivity. These findings highlight the critical role of climate variables in shaping durian productivity and stress the importance of adaptive strategies to ensure sustainable agricultural output.
Keywords: agricultural productivity; climate change; durian harvest; Land surface temperature (LST); NDVI